2021
DOI: 10.1017/epi.2021.40
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice in Testimonial Justification: A Hinge Account

Abstract: Although research on epistemic injustice has focused on the effects of prejudice in epistemic exchanges, the account of prejudice that emerges in Fricker's (2007) view is not completely clear. In particular, I claim that the epistemic role of prejudice in the structure of testimonial justification is still in need of a satisfactory explanation. What special epistemic power does prejudice exercise that prevents the speaker's words from constituting evidence for the hearer's belief? By clarifying this point, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The growing literature in "hinge epistemology," upon which I cannot expand here, shows how productively this notion can be employed for a variety of purposes, from the rebuttal of the skeptical challenge to the study of social phenomena such as testimonial justification, disagreement, or trust. 17 In social epistemology, I recently suggested that this notion helps to demonstrate how prejudice works in testimonial injustice (Boncompagni 2021a). I want to argue that it can also be applied to the study of hermeneutical injustice, especially in the context of identities.…”
Section: Changing the Metaphor: From Gaps To Hingesmentioning
confidence: 99%
“…The growing literature in "hinge epistemology," upon which I cannot expand here, shows how productively this notion can be employed for a variety of purposes, from the rebuttal of the skeptical challenge to the study of social phenomena such as testimonial justification, disagreement, or trust. 17 In social epistemology, I recently suggested that this notion helps to demonstrate how prejudice works in testimonial injustice (Boncompagni 2021a). I want to argue that it can also be applied to the study of hermeneutical injustice, especially in the context of identities.…”
Section: Changing the Metaphor: From Gaps To Hingesmentioning
confidence: 99%
“… These propositions are epistemic and ontological, but several philosophers have extended the notion of hinge commitments so that there can be moral, social or even political hinges. See (Ashton, 2019), (Boncompagni, 2021), (Coliva, 2015) and (Ranalli, 2022). …”
mentioning
confidence: 99%
“… See Christensen & Lackey (2013) andFeldman & Warfield (2010).5 These propositions are epistemic and ontological, but several philosophers have extended the notion of hinge commitments so that there can be moral, social or even political hinges. See(Ashton, 2019),(Boncompagni, 2021),(Coliva, 2015) and(Ranalli, 2022).6 Albeit this leaves it open that one might have evidence for a hinge commitment (Neta, 2019). defends this view (Hazlett, 2006).…”
mentioning
confidence: 99%